(untitled) (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: Identify the learning of Pancasila values in Civics subjects in junior high schools, and identify problems with learning Pancasila values in Civics subjects and efforts to solve them in junior high schools. Methodology: This type of research is descriptive with a qualitative approach. The subjects of this research were school principals, citizenship education teachers, and students. Data collection techniques in this research used interviews, classroom observations, and documentation. The data validity checking technique uses triangulation with data sources from interviews, class observations, and documentation. Data analysis uses qualitative analysis. Main Findings: The discovery in this research is that learning Pancasila values in Citizenship Education subjects at junior high school uses various models that vary in each lesson, such as the model of teaching values in direct teaching, student involvement, and critical pedagogy. The obstacles faced in learning Pancasila values in civics subjects at junior high schools are environmental factors, limited learning time, limitations of learning media, and the classroom climate, which is not conducive when learning takes place. Third, the efforts made to overcome obstacles to learning Pancasila values are that teachers try to approach students, provide an example to all school members, and utilize time as optimally as possible to achieve learning objectives. Novelty/Originality of this study: The efforts made by teachers to deal with the obstacles they face, teachers try to approach students and provide an example to all school members. Utilize time as optimally as possible so that learning objectives are achieved.